PENGARUH PENAMBAHAN EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP KANDUNGAN PROTEIN, pH,RENDEMEN DAN SIFAT ORGANOLEPTIK PADA DAGING SE’I SAPI: Effect of Adding Red Dragon (Hylocereus Polyrhizus) FruitExtract on Protein Containment, pH, Rendement and Organoleptic of Beef Se'i - Devilia Ndua Awa; Geertruida Margareth Sipahelut; Bastari Sabtu; Tri Rizkie Zainal (Faculty of Animal Science, University of Tulang Bawang, 2025)
This study aims to determine the effect of the addition of red dragon fruit peel extract (Hylocereus polyrhizus) on the quality of beef se'i meat. The method used was a completely randomized design (CRD), consisting of 4 treatments and 4 replicates, resulting in 16 experimental units. The addition of red dragon fruit peel extract consisted of treatments P0 (0%), P1 (5%), P2 (10%), and P3 (15%). The parameters measured in the study were protein content, pH, yield, and organoleptic properties, including color, aroma, taste, and tenderness. Statistical test results showed that the provision of red dragon fruit peel extract had a very significant effect (P < 0.01) on color, aroma, taste, and tenderness, while it had a significant effect (P < 0.05) on protein content and no significant effect (P>0.05) on pH and yield. Based on the results of the study, it can be concluded that the effect of adding 15% red dragon fruit peel extract can increase protein content, color, aroma, taste, and tenderness in beef se'i meat, while the pH and yield do not change. Keywords: Beef se'i, Organoleptic, Protein content, pH, Red dragon fruit skin